Versatile light-responsive organogels: Evaluation of their dye releasing and photoinitiation behaviors - Dashan, Irem; Elverici, Melisa; Balta, Demet Karaca; Temel, Binnur Aydogan; Temel, Gokhan (WILEY, 2019)
Light-responsive crosslinked structures were prepared by a straightforward quaternization strategy using chloride functional polystyrene copolymers and commercially available Michler's ketone with varying feed ratios. Resulting organogels demonstrated excellent solvent absorption and their swelling characteristics were altered by UV-light irradiation. According to scanning electron microscope images, UV-illuminated samples showed an obvious photodecomposition, which enhanced their solvent uptake capacity with increase of UV exposure. Additionally, release behavior of eosin Y as a model compound was determined by UV-vis and fluorescence spectrometers. Achieved photoactive gels were also employed as the reusable heterogeneous initiators for photoinduced free-radical polymerization of methyl methacrylate. (c) 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 1275-1282
Keywords: dye release; organogel; photodecomposition; photopolymerizaton; light-responsive gel; DRUG-DELIVERY; POLYMERIZATION; NANOPARTICLES; HYDROGELS; COPOLYMERIZATION; POLYACRYLAMIDE; POLYMERS; NANOGELS; ACID; UV; Polymer Science